Anomalous optical saturation of low-energy Dirac states in graphene and its implication for nonlinear optics. (17th May 2019) - Semnani, Behrooz; Jago, Roland; Safavi-Naeini, Safieddin; Majedi, Hamed; Malic, Ermin; Tassin, Philippe
Abstract: We reveal that optical saturation of the low-energy states takes place in graphene for arbitrarily weak electromagnetic fields. This effect originates from the diverging field-induced interband coupling at the Dirac point. Using semiconductor Bloch equations to model the electronic dynamics of graphene, we argue that the charge carriers undergo ultrafast Rabi oscillations leading to the anomalous saturation effect. The theory is complemented by a many-body study of the carrier relaxations dynamics in graphene. It will be demonstrated that the carrier relaxation dynamics is slow around the Dirac point, which in turn leads to a more pronounced saturation. The implications of this effect for the nonlinear optics of graphene are then discussed. Our analysis shows that the conventional perturbative treatment of the nonlinear optics, i.e. expanding the polarization field in a Taylor series of the electric field, is problematic for graphene, in particular at small Fermi levels and large field amplitudes.